O Programa Nacional de Alimentação Escolar e as compras da agricultura familiar por municípios do Ceará - Gomes, Ludmir dos Santos (2023)
Study about the school feeding theme, specially the family farming purchases for the School Feeding National Program (PNAE). The research issue starts from the following hypothesis: there are determinants from political, cultural and educational nature, with the latter related to the limited access to the knowledge (PNAE’s rules, laws and technical standards), which prevent the family farmers and municipalities from meeting the legal requirements of the family farming purchases for the school feeding, as determined by the article 14 from the Law Nº 11.947/2009. The general objective is to investigate the food purchase process, from the family farming and its organizations to the PNAE of municipalities from the Ceará State (Executing Agencies – Eex), between 2018 and 2023. The specific objectives are: identifying the improprieties and inadequacies related to the family farming purchases, as found by the Eex monitoring and advising activities made by the Collaboration Center for School Food and Nutrition (CECANE), from the Federal University of Ceará (UFC), in the years 2018 to 2021, describing its characteristics; verifying to which point these frailties compromise the PNAE’s objective of helping the social, economic and cultural local development; pointing educational interventions and strategies favorable to the equation of the barriers that compromise the full insertion of the family farmers and their organizations in the food supply process to the school feeding. Methodology: 1) Document analysis source: documents produced by the CECANE, UFC and the Education Development National Fund (FNDE); 2) speech/ideas: source: farmers who are PNAE suppliers. The data was collected through surveys and interviews and analyzed based on PNAE legislation and standards and the theory about the sustainable development. Results: In the Ceará State, the PNAE is still seeking to be established as an effective sustainable development strategy, characterized by improvements and obstacles. It works in the midst of a maze of issues that make it a little inclusive strategy to the family farming. It faces inadequacies from its regulations and objectives to reach. It reproduces the contradictions from the social and political model, which turns it vulnerable to practices which exceed a lot the bounds of the legality, impersonality, morality and publicity, as constitutionally provided.